Revalorización del área Central - Kullock, David; Vicente, Olga (2001)
Programa Ordenamiento del Area Central de Bs.As.
Keywords: AREAS CENTRALES; PLANES URBANISTICOS; ARGENTINA; BUENOS AIRES; PLANIFICACION URBANA